Comparative Analysis of Salinity Readings for Water Quality Monitoring between IoT-Based Sensor Systems and Refractometer - Hadi Hariyanto; Gilang Ramadhan (Departemen Sistem Informasi, Fakultas Teknologi Informasi, Universitas Andalas, 2025)
Salinity is among the factors that affect aquaculture water quality, along with pH, temperature, dissolved oxygen (DO), and ammonia. The osmotic pressure is influenced by salinity, which directly affects the aquatic biota. An osmotic pressure increases with increasing salinity in a body of water. The threshold salinity varies between aquatic biotas. If there is an isoosmotic pressure, the aquatic biota will thrive. Specific gravity, electrical conductivity (EC), light refraction, and chlorine titration are commonly used in salinity tests. Refractometer light refraction and water quality monitoring (WQM) salinity sensor EC were the salinity measurements employed in this research. In general, difficulties experienced while employing EC measurements to the tool's accuracy and precision. The salinity sensor was evaluated and verified in this research by comparing the findings of WQM readings with a refractometer over a three-day term. The sensors of 22 WQM devices were tested and validated in 22 BLUPPB (Balai Layanan Usaha Produksi Perikanan Budidaya, Aquaculture Production Business Service Center) ponds. The WQM was put in the center of the pond, and salinity was measured with a refractometer at four spots around the pond's edge. On the first trial, the WQM error and accuracy values were 19.90% and 80.10%, respectively; on the second trial, they were 9.58% and 90.42%, and on the third attempt, they were 16.21% and 83.79%. WQM accuracy was 0.7128, 0.7285, and 0.7174 on the first, second, and third time